Prenatal diagnosis of chromosomal aberrations in fetuses with conotruncal heart defects by genome-wide high-resolution SNP array. (2nd April 2020) - Lin, Meifang; Zheng, Ju; Peng, Ruan; Du, Liu; Zheng, Qiao; Lei, Ting; Xie, Hongning
Abstract: Objectives: To explore chromosomal variations, including copy number variations (CNVs), in fetuses with conotruncal heart defect (CTD). Methods: During a 5-year period, a total of 129 fetuses with ascertained CTDs were investigated for chromosomal abnormalities using quantitative fluorescence PCR (QF-PCR) and chromosomal microarray analysis (CMA). Fetuses were divided into two subgroups: benign group (with normal QF-PCR results and benign CNVs) and nonbenign group [with aneuploidies, nonbenign CNVs [pathogenic CNVs and CNVs of unknown significance (VOUS)]. Data on fetal structural malformations, chromosomal variations, and pregnancy outcomes were collected and compared. Results: Of the 129 cases, 17 were found to have common aneuploidies. In the remaining 112 cases with normal a QF-PCR result, pathogenic CNVs, CNVs of VOUS, and benign CNVs were identified in 5.3, 5.3, and 4.5%, respectively. Compared with benign group, fetuses in nonbenign group had a significantly higher rate of neurologic defects (13.8 versus 3.0%, p  < .05), overall extracardiac anomalies (86.2 versus 45.0%, p  < .05), and perinatal death (57.1 versus 18.4%, p  < .05), whereas, no significant difference in that of associated cardiovascular anomalies was noted (48.2 versus 46.0%, p  = .29). Among the extracardiac anomalies, thymus abnormalities were strongly associated with nonbenign CNVs (33.3 versus 1% of fetuses in benign group, p  < .05). Conclusions: Pathogenic CNVs, in addition to chromosomal aneuploidies, contributed to the pathogenesis of CTD. The presence of associated extracardiac anomalies including thymus abnormalities correlated with a higher probability of nonbenign chromosomal variations, which was associated with an unfavorable outcome.